Assembly and structure of protein phosphatase 2A - Shi, YiGong (Science China. Life sciences, 2009)
Protein phosphatase 2A (PP2A) represents a conserved family of important protein serine/threonine phosphatases in species ranging from yeast to human. The PP2A core enzyme comprises a scaffold subunit and a catalytic subunit. The heterotrimeric PP2A holoenzyme consists of the core enzyme and a variable regulatory subunit. The catalytic subunit of PP2A is subject to reversible methylation, medi-ated by two conserved enzymes. Both the PP2A core and holoenzymes are regulated through interac-tion with a large number of cellular cofactors. Recent biochemical and structural investigation reveals critical insights into the assembly and function of the PP2A core enzyme as well as two families of holoenzyme. This review focuses on the molecular mechanisms revealed by these latest advances.